2010
DOI: 10.4317/medoral.15.e340
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral epithelioid hemangioendothelioma: A case report and review of the literature

Abstract: The epithelioid hemangioendothelioma (EH) is an uncommon angiocentric neoplasm of borderline or intermediate malignant potential, between the hemangioma and conventional angiosarcoma. It is characterized by the proliferation of endothelial cells with epithelioid or histiocitóide morphology with vacuolated cytoplasm and occasional eosinophilic spindle cells. Shows potential for local recurrence as well as the ability to metastasize. Rarely affects the oral cavity, it have been described from 1975 until 2008 onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Both are low-grade vascular sarcomas that can be readily distinguished from epithelioid angiosarcoma by their characteristic histologic and clinicopathologic features. A previous review detected 27 oral epithelioid hemangioendotheliomas reported from 1975 to 2008 [14]. Most originated in the gingiva and less frequently in the tongue, but only 1 case involved the palate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Both are low-grade vascular sarcomas that can be readily distinguished from epithelioid angiosarcoma by their characteristic histologic and clinicopathologic features. A previous review detected 27 oral epithelioid hemangioendotheliomas reported from 1975 to 2008 [14]. Most originated in the gingiva and less frequently in the tongue, but only 1 case involved the palate.…”
Section: Discussionmentioning
confidence: 95%
“…All of these metastatic deposits were minute bleeding lesions, and none of them was compatible with a primary tumor. Rare low-grade variants of malignant vascular neoplasms reported as tonsillar or intraoral primary include epithelioid [14] and kaposiform [15] hemangioendothelioma. Both are low-grade vascular sarcomas that can be readily distinguished from epithelioid angiosarcoma by their characteristic histologic and clinicopathologic features.…”
Section: Discussionmentioning
confidence: 99%
“…The literature highlights that lesions in the upper gingiva and oral mucosa are the ones that most relapse (8,10,13,32) . According to this data, it is particularly worth mentioning one case in this series, a 7 year-old patient who presented HEE relapse in the upper gingival ridge with adjacent bone destruction two years after the first surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, this neoplasia, characterised by the presence of endothelial cells with a large amount of eosinophilic cytoplasm similar to histiocytes, contains cords and blocks of epithelioid endothelial cells, sometimes intumescent and located inside a fibromixoid stroma 3. Due to the predominant morphological characteristics, the EHEs can be confused with other lesions including haemangioma to squamous cell carcinoma, therefore, emphasises the importance of immunohistochemical analysis to establish the definitive diagnosis 7 8. These tumours are immunopositive for markers of vascular differentiation such as CD34, factor VII or the CD 31 and negative for markers of neuronal or muscular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the metaplastic bone formation with significant cellular atypia, mitotic activity greater than one per 10 highpower fields, an increased proportion of spindle tumour cells and focal necrosis represents histopathological factors associated with a more aggressive behaviour of the lesion 5 7. Other clinicopathological parameters, such as tumour size, localisation and the presence of mucosal ulcerations are not considered to be statistically relevant to the biological behaviour of the neoplasia 5.…”
Section: Discussionmentioning
confidence: 99%